Strategi Pengembangan Sumber Daya Manusia, Keunggulan Kompetitif, dan Kompensasi dalam Meningkatkan Kinerja Guru Sekolah - Nina Wahyuni Siregar; Amini Amini; Zulaspan Tupti (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2024)
The compensation given to teachers is still relatively low so it will have an impact on teacher performance which is not as expected. This research aims to answer the problem, namely, how to develop human resources, competitive advantage and compensation carried out by the Al Washliyah 3 Medan teacher school, Madrasah Aliyah SMK Business Management in improving performance teachers. This research is qualitative research with a case study type. The analysis technique in this research uses SWOT analysis to produce strategies that must be implemented by the three schools. The results of this research show that the human resource development carried out by the three schools has gone quite well but still has several shortcomings and requires improvement for future development. The compensation system established by the school is analyzed into a SWOT matrix which produces many things that need to be improved, such as improving the quality of the workforce, increasing the minimum education level of bachelor’s degree, increasing the number of certified teachers, improving facilities and infrastructure, mastering IT, improving learning methods, and increasing nominal income, that the teacher will accept.